Teaching standard English to nonstandard speakers: Some methodological issues - Craig, Dennis R.
This article discuses findings of previous studies concerning the teaching of Standard English to non-standard speakers. It examines implications of, and possible solutions to, the problem of negative attitudes in language learning. It stresses the need for resource materials that incorporate principles and methodologies of language arts instruction for non-standard speakers
Keywords: Creole speakers